A randomised controlled trial of combined EEG feedback and methylphenidate therapy for the treatment of ADHD (Swiss Medical Weekly, 2013)
PURPOSE: To evaluate the efficacy of combined methylphenidate and EEG feedback treatment for children with ADHD. METHODS: Forty patients with ADHD were randomly assigned to the combination group (methylphenidate therapy and EEG feedback training) or control group (methylphenidate therapy and non-feedback attention training) in a 1:1 ratio using the double-blind method. These patients, who met the DSM-IV diagnostic criteria and were aged between 7 and 16 years, had obtained optimal therapeutic effects by titrating the methylphenidate dose prior to the trial. The patients were assessed using multiple parameters at baseline, after 20 treatment sessions, after 40 treatment sessions, and in 6-month follow-up studies. RESULTS: Compared to the control group, patients in the combination group had reduced ADHD symptoms and improved in related behavioural and brain functions. CONCLUSION: The combination of EEG feedback and methylphenidate treatment is more effective than methylphenidate alone. The combined therapy is especially suitable for children and adolescents with ADHD who insufficiently respond to single drug treatment or experience drug side effects.